Two Extensive Margins of Credit and Loan‐to‐Value Policies. Issue 7 (15th September 2016) - GETE, PEDRO; REHER, MICHAEL
Abstract : We analyze a model of mortgage markets, housing tenure choice, heterogeneous agents, and default with closed form solutions. We uncover new insights which may inspire empirical work, and we ground already established insights in a series of tractable expressions. Then we study optimal loan‐to‐value (LTV) regulation and show that the choice of an LTV cap should balance the opposing forces of access to homeownership and the negative externalities associated with default. Homeownership affordability concerns induce procyclical elements into optimal regulation which attenuate the countercyclical regulation justified by the negative default externalities.